Violence Ontology in Pierre Bourdieu’s Perspective and Its Relevance to Violence Phenomenon among Religious Society in Indonesia - Muh. Abdi Goncing (JICSA : Journal of Islamic Civilization in Southeast Asian, 2013)
This article discusses how Pierre Bourdieu’s viewpoint on violence ontology and its relevance to violence phenomenon toward Indonesia’s society. According to Pierre that violence is form of domination to the human itself taking place subtly and not realizing that has become a form of habit in human life. Within the context of Indonesian, it can be involving violence between religious society in this country, or it can be specified over again into the society who embraces Islam. A new violence is actually a practice of domination conducted by the parties who think they are the only one true and majority in order to perpetuate the truth dominance of religion. In other words, the violence can only be understood as a form of domination to the other religions teachings, especially for the teaching or religion categorized as a minority religion or belief – in this case of Muslim and non- Muslim community.